OsPDIL1-5: dual role in promoting growth and development while modulating drought stress tolerance in rice (Oryza sativa L.) - Chen, Jilin; Zhang, Jin; Fang, Chao; Ren, Lijun; Lan, Tong; Wu, Weiren; Lan, Tao (Frontiers in Plant Science, 2024)
Drought tolerance and plant growth are critical factors affecting rice yield, and identifying genes that can enhance these traits is essential for improving crop resilience and productivity. Using a growth-depressed and drought-tolerant (gddt) mutant of the indica rice variety Huanghuazhan (HHZ) generated by radiation mutagenesis, we discovered a novel gene, GDDT, which plays a dual role in plant biology: it acts as a positive regulator of growth and development, but as a negative regulator of drought resistance. The gddt mutant displayed a marked reduction in plant growth and seed setting rate, yet exhibited an unexpected advantage in terms of drought tolerance. Our research revealed that the enhanced drought tolerance of the gddt mutant is primarily due to a decrease in stomatal size, density, and aperture, which reduces water loss, and an activation of the reactive oxygen species (ROS) scavenging system, which helps protect the plant from oxidative stress. These physiological changes are observed both under drought conditions and in normal growth conditions. This discovery highlights the importance of GDDT as a pleiotropic gene with significant implications for both plant growth and drought resistance. Through map-based cloning, we determined that the protein disulfide isomerase-like (PDIL) gene OsPDIL1-5 is the GDDT gene. The protein encoded by this gene was localized to the endoplasmic reticulum, consistent with its predicted function. Our findings provide new insights into the role of PDIL genes in rice and suggest that further study of GDDT could lead to a better understanding of how these genes contribute to the complex interplay between plant growth, development, and stress responses. This knowledge could pave the way for the development of rice varieties that are more resilient to drought, thereby increasing crop yields and ensuring food security in water-limited environments.